Participatory rural appraisal approaches: an overview and an exemplary application of focus group discussion in climate change adaptation and mitigation strategies - Uddin, MN; Anjuman, N (International Journal of Agricultural Research, Innovation and Technology, 2014)
Different tools and techniques of participatory approaches are the basic way of conducting qualitative research especially in the field of applied social science. Focus Group Discussion (FGD) is one of the main Participatory Rural Appraisal (PRA) technique often used in combination with others to achieve desired goals. Considering this concept, this paper attempts to review the PRA approach and then application of FGD, in combination with matrix scoring and ranking to identify problems and causes of climate change along with possible mitigation and adaptation strategies. A group of 20 students at post graduate level under the faculty of Agriculture and Horticulture at Humboldt University of Berlin, Germany those from different corner of the world was considered as target people of the study. The results concluded that unpredictable weather events was ranked as the present outstanding visible climate change problem caused by human activities. However, it was noted that if alternative renewable energy sources are exploited, this could contribute to solving the present climate change problem. This finding might have the good reference for the policy makers in the same line not only for developing countries but also for developed countries. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17848 Int. J. Agril. Res. Innov. & Tech. 3 (2): 72-78, December, 2013